Seasonal environmental parameters influence biochemical responses of the fiddler crab Minuca rapax to contamination in situ - Vellosa Capparelli, Mariana (2019)
The mudflat fiddler crab Minuca rapax, typical of mangroves and intertidal zones in the Western Atlantic Ocean, responds to fluctuations in environmental parameters by biochemical and physiological adjustments. Such biochemical effects are commonly employed in environmental studies as biomarkers of estuarine contamination. This study evaluates biochemical responses in the gills and hepatopancreas of M. rapax in situ from localities exhibiting different types and levels of contamination, against a backdrop of fluctuations in environmental parameters like salinity and temperature common to estuarine regions. The biochemical biomarkers metallothionein (MT)-like protein titers and glutathione S-transferase (GST), glutathione peroxidase (GPx) and acetylcholinesterase (AChE) activities were used to evaluate responses to environmental contamination and seasonal changes in environmental parameters. Crabs were collected during two seasons, the austral winter and summer, at three sites along the coast of the state of São Paulo, Brazil that present decreasing degrees of environmental contamination: Ilha Diana, Santos (ID) > Rio Itapanhaú, Bertioga (RI) > Picinguaba, Ubatuba (P), a pristine control site. Our findings show that MT were induced in crabs from the contaminated sites (ID and RI) mainly during winter, revealing the activation of detoxification mechanisms; however MT were also induced in P crabs during the summer rainy season. GPX, GST and AChE activities were altered in P crabs during summer and in ID and RI crabs in winter. While enzyme activities in summer crabs may reflect seasonal changes in precipitation and salinity, in winter these altered activities appear to reflect contamination, although an effect of environmental parameters cannot be excluded. These findings reveal a strong seasonal influence on biochemical biomarker responses in Minuca rapax, a relevant factor to consider when interpreting the impact of environmental contamination in estuaries.